Is elastic stable intramedullary nail a good choice for pathological fractures of the proximal femur due to simple bone cyst in pediatric population?. Issue 39 (25th September 2020) - Li, Jin; Ze, Renhao; Rai, Saroj; Tang, Xin; Liu, Ruikang; Hong, Pan
Abstract : Abstract: Pathological fracture of the proximal femur represents a challenging situation for orthopedic surgeons because of the high risk of non-union, varus union, and avascular necrosis (AVN) of the femoral head. This study aims to investigate the efficacy of ESINs for the treatment of proximal femoral fractures caused by simple bone cysts (SBCs). All the patients with a diagnosis of proximal femoral fracture secondary to SBC treated with ESINs combined with bone grafting between January 2008 and January 2018, were analyzed retrospectively. In all, 11 patients were included in the Double ESINs group (5.1 ± 0.8 years, 5 male, 6 female) and 27 patients were included in the Triple ESINs group (9.1 ± 2.1 years, 11 male, 16 female). There was no significant difference between the 2 groups concerning the patients demographic parameters, including sex and affected side. However, the age in the Double group was significantly younger than those in the Triple group ( P  < .001). All patients in both groups displayed excellent outcomes according to the Musculoskeletal Tumor Society Score (MSTS), and there was no significant difference between the 2 groups at a 12-month follow-up evaluation ( P  = .10). As for the Capanna classification (1 + 2), there was no significant difference between these 2 groups ( P  = .24). In the Triple ESINs group, 24 (88.9%) patients were categorized in Capanna 1 and 2, whereas all patients in Double ESINs were Capanna 1 and 2. Overall, the success rate was 92%. ESINs combined with bone grafting is a successful strategy for proximal femoral fractures caused by SBCs in the pediatric population.